2015
DOI: 10.1371/journal.pone.0143204
|View full text |Cite|
|
Sign up to set email alerts
|

Gonadal Transcriptome Analysis in Sterile Double Haploid Japanese Flounder

Abstract: Sterility is a serious problem that can affect all bionts. In teleosts, double haploids (DHs) induced by mitogynogenesis are often sterile. This sterility severely restricts the further application of DHs for production of clones, genetic analysis, and breeding. However, sterile DH individuals are good source materials for investigation of the molecular mechanisms of gonad development, especially for studies into the role of genes that are indispensable for fish reproduction. Here, we used the Illumina sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Previously, we also did a comprehensive comparison of gene expression in fertile and sterile ovaries of DH Japanese flounders by transcriptome sequencing and found that the reduced levels of expression of genes involved in steroid biosynthesis might affect the development of the ovary (Zhang et al, ). Herein, we compared the hormone levels in sterile and fertile DH flounders and observed that compared to fertile DH flounders, in sterile DHs, the levels of hormones related to reproductive process were lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we also did a comprehensive comparison of gene expression in fertile and sterile ovaries of DH Japanese flounders by transcriptome sequencing and found that the reduced levels of expression of genes involved in steroid biosynthesis might affect the development of the ovary (Zhang et al, ). Herein, we compared the hormone levels in sterile and fertile DH flounders and observed that compared to fertile DH flounders, in sterile DHs, the levels of hormones related to reproductive process were lower.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis of ovary samples from DH Japanese flounders revealed that reduced expression of genes involved in steroid biosynthesis might affect the development of ovaries (Zhang et al, ). As a result, pertinent questions that warrant in‐depth study and discussion have been raised about the differences in the hypothalamus and pituitary between sterile DHs and fertile flounders.…”
Section: Introductionmentioning
confidence: 99%
“…Similar situation was observed in tilapia where a few gynogenetic females have been found to produce viable eggs (Müller‐Belecke & Hörstgen‐Schwark, ). In Japanese flounder, most of the DH females were sterile with varying levels of dysgenesis (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, clonal lines have been generated in a limited number of fish species due to the low survival of DHs and disturbances during their gonadal development and oogenesis (Hou et al, ; Hou, Fujimoto, Saito, Yamaha, & Arai, ; Kato et al, ; Kobayashi, Ide, Hiasa, Fushiki, & Ueno, ; Komen, Bongers, Richter, Van Muiswinkel, & Huisman, ; Naruse, Ijiri, Shima, & Egami, ; Sarder, Penman, Myers, & McAndrew, ; Yamamoto, ; Young, Wheeler, Fields, & Thorgaard, ; Zhang et al, ). DH females may be sterile or produce poor quality eggs exhibiting decreased ability to be fertilized and impaired competences for the proper development of embryos (Migaud et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Cacot et al 2003;Viveiros et al 2002), to activation of the complete processes as seen in eels (see section below) and golden rabbitfish (Siganus guttatus; Komatsu et al 2006). Although, in some species Fsh has been shown to induce the full process of spermatogenesis and spermiation (Mazón et al 2014;Zhang et al 2015a;Chu et al 2015), most hormonal treatments have used Lh preparations, which acts on the gonad level or GnRH´s, which have the effect of Lh release from the pituitary (Mylonas et al 2017). A commonly used Lh preparation is pituitary extracts (PEs) from spawning fish (commonly carp or salmon).…”
Section: Artificial Manipulation Of Teleost Sexual Maturationmentioning
confidence: 99%